As reconfigurações do trabalho docente no século XXI: controle, intensificação e precarização do professor - Vieira, Renato Gomes (2019)
This thesis, entitled The reconfiguration of teaching work in the 21st century: control, intensification and precariousness of the teacher, is linked to the research line Work, Employment and Unions of the Graduate Program in Sociology of the Federal University of Goiás (UFG). It is a research that seeks to show how teaching work has been reconfiguring because of the great transformations of the contemporary world, which had its development since the 1980s. Its main problem is: the contemporary reconfigurations of capitalism, notably the restructuring brought about an increase in the intensification, control and precariousness of the teaching work of the basic education teacher in Brazil in the last thirty years? To answer this problem, we start from the hypothesis that the teaching work has been reconfigured by the changes of contemporary capitalism mentioned here: productive restructuring and neoliberalism. And these phenomena have been forcing workers of all categories, including education, more control, more intensification and more precarious working conditions. Each of these processes brought about profound social, political, and economic changes, so that the education, school, and work of the teacher were not far from these mutations. Theoretical and empirical research can realize that the work of female teachers is increasingly intensified from the physical, intellectual and emotional point of view, due to more work and daily demands. The increased control over his work appears very clearly, in various aspects that imply more vigilance over the teacher in the exercise of his profession. And, finally, the precariousness of working conditions, which persists in reality, wage and working conditions in schools. Although it remains a work that has many specific traits of work on another human being, these processes of rationalization have strongly affected the life of teachers.